Integrasi Office Automation System Dalam Meningkatkan Produktivitas Kerja Karyawan PT X - Rara Mutiara Sopari; Wiwi Darojatul Alawiyah (Jurnal Transformasi Bisnis Digital, 2024)
In a business environment, a company will definitely look for ways to improve employee performance and productivity. To increase employee productivity, of course, companies must optimize facilities and infrastructure to support employee productivity. The use of facilities and infrastructure such as office automation system technology is used to facilitate activities in office processes, increase efficiency in work, reduce errors caused by humans. This research examines the use of office automation systems at PT X in supporting office operational work. The research process uses a qualitative approach with literature studies through previous research in the form of relevant journals and theories to obtain secondary data. This research took place for 1 month from April 2024 to May 2024. The results showed that the integration of automation systems at PT X had an impact on a significant increase in employee productivity and performance. The results of this study are expected to be an impetus for other organizations to adopt the use of automation technology in an effort to improve the productivity and performance of their employees, and produce a positive impact on the entire organization.